Direct and sulfide mediated treatment of textile effluents in acetate and ethanol-fed upflow sulfidogenic bioreactors - Yilmaz, T.; Yildiz, M.; Yapici, C. S. Arzum; Annak, H. U.; Ucar, D. (Springer, 2023)
Sulfate is a key component in the textile industry and sulfate-reducing conditions could enhance dye reduction in the treatment of textile industry wastewater. In this study, a sulfidogenic up flow anaerobic reactors fed with different organic substrates (ethanol and acetate) were operated to treat textile wastewater and Remazol Brilliant Violet 5R was used as a model dyestuff. The reactors were operated for 192 days at 7 operational periods at 1 day HRT. Throughout the study, 2000 mg/L SO42- and 1340-1540 mg/L COD were added to the feed, corresponding to COD/SO42- ratios of 0.67 and 0.77, respectively. Remazol Brilliant Violet 5R was added to feed at a concentration of 50 mg/L on day 148 and its concentration was gradually increased to 1000 mg/L. The maximum dye removal rate was over 990 mg/(L.d) for both reactors. Although high-rate dye removal was achieved, an increase in the dye concentration resulted in a decreased sulfate reduction and COD oxidation for both reactors. In addition to the continuous process, biotic and abiotic batch reactors were operated to identify the dye removal mechanism. Batch reactors showed that biogenic sulfide produced in the sulfate reduction can be used to reduce Remazol Brilliant Violet 5R. Batch reactors also indicated that although abiotic sulfide-based Remazol Brilliant Violet 5R reduction is possible, the presence of microorganisms increased its reduction rate.
Keywords: Sulfide-based reduction; Azo dye; Decolorization; Sulfidogenic reactor